How effective are interventions in optimizing workplace mental health and well-being? A scoping review of reviews and evidence map - Alex Waddell; Breanne Kunstler; Alyse Lennox; Loyal Pattuwage; Emily AC Grundy; Diki Tsering; Patrick Olivier; Peter Bragge (Nordic Association of Occupational Safety and Health (NOROSH), 2023)
OBJECTIVES: Mental well-being is critical to quality of life. Workplace mental well-being is crucial to ensure employee health, satisfaction, and performance. Mental ill-health is a global challenge, costing workplaces $17 billion per year. Workplaces have realized the need for investment in interventions to promote mental health and well-being in their workforce. However, given their limited resources, workplace personnel responsible for program implementation need evidence-based guidance on which interventions influence which outcomes.METHODS: This study employed a scoping review methodology in order to produce an evidence map and includes reviews of workplace mental well-being interventions. The search strategy focused on peer-reviewed articles with the primary aim of investigating workplace mental health interventions. Reviews were assessed for quality using AMSTAR 2. The evidence map includes interventions (rows) and outcomes (columns), with the relative size of the reviews underpinning each intersection represented by circles and the direction of evidence represented by color.RESULTS: Eighty reviews were deemed eligible from 4795 citations. The resulting evidence map includes 17 intervention types designed to influence 12 outcomes. Interventions with the highest quality evidence were mindfulness, education and information provision, and individual psychological therapies. The most common outcomes were burnout / stress reduction and mental well-being. Interventions tended to focus on individual level factors rather than organizational or system-level factors.CONCLUSION: The evidence-base for workplace mental health interventions is broad and extensive. There is an apparent knowledge-to-practice gap, presenting challenges to implementing workplace mental health programs (ie, what interventions have the highest quality evidence). This study aims to fill the gap by providing an interactive evidence-map. Future research should look to fill the gaps within the map including the lack of organization and system level factors and especially economic evaluations.